ANALYSIS OF CUSTOMER SATISFACTION IN COMPUTER TRAINING INSTITUTIONS USING C4.5 ALGORITHM - Surahmat, Asep (Scientific Journal of Information System, 2023)
Customer satisfaction is an important reference in the sustainability of a business, as is the case with the computer training business at Radar Education Center which has competitors in its business. Until now there is no measuring tool for customer satisfaction at the Radar Education Center, this problem will be solved through the Decision Tree method using the C4.5 algorithm to analyze customer satisfaction. The data used comes from Radar Education Center customer data which consists of 80% training data and 20% testing data. After calculating accuracy using the Confusion Matrix, the Class Precision value was "yes" 83.33% and Class Recall "yes" was 100%.